LEGAL DILEMMA OF CONSUMER PROTECTION UNDER ALGORITHMIC PRICING REGIME: Pricing Algorithms - Ugochukwu Ehirim (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2026)
The emergence of smart technologies has introduced machine learning algorithms with progressive capacities to predict the category of goods a particular class of persons may purchase, and within a determined price range, a development which has threatened the cardinal principles of privacy and pricing equity, thereby posing ethical and legal challenges.The prospect that algorithms could promote efficiency by promoting market optimisation dwindles with the grievous harm suffered by consumers from a lack of pre-information and behavioural biases disproportionately affecting identifiable consumer groups. This paper examines the efficiency of the current regulations on data governance and consumer-privacy protection, highlighting the need to balance regulation with the progressive social values of artificial intelligence (AI) technologies through the evolution of algorithm-centred approaches. It adopts the doctrinal methodology of juridical research to analyse primary and secondary source materials. It is demonstrated that most pricing-algorithms discreetly defy the GDPR applicable to Europe and its legislative transplantations, including the Nigeria Data Protection Act (NDPA) which primarily protect consumers’ rights within community Europe and Nigeria, respectively. It proposes the following solutions, among others: i) the liberalisation of policing-algorithms and other monitoring tools to enable users and civil society to effectively track breaches of consumers’ rights and extant laws; ii) synergy among regulatory agencies across sovereign boarders; iii) Adoption of China’s cutting-edge policy unmasking the black-box for proper interpretation of AI decision-making process. These measures would streamline the battlefield with precision regarding the limits of AI's intervention with market forces and consumers’ liberties.